2019
DOI: 10.3897/phytokeys.130.34555
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Gastrochilus prionophyllus (Vandeae, Orchidaceae), a new species from Yunnan Province, China

Abstract: Gastrochilus prionophyllus, which was previously not validly published, is here validated. The species is described along with illustration and photos. Morphologically, the long and pendulous stem and distichous leaves of this new species indicate that it belongs to the sect. Microphyllae. It is unique in having thick fleshy leaves and margin significantly serrate, small flowers, reniform epichile and margin with dentations, thickened cushion on the central epichile and subconic hypochile. Meanwhile, a prelimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…We collected specimens of five previously unidentified species during our field surveys in Yunnan and Tibet from 2016–2023. Following a review of the literature (see Pearce and Cribb 2002 ; Chen et al 2009 ; Raskoti 2009 ; Jin and Pang 2016 ; Averyanov et al 2018 ; Wu et al 2019 ; Mu et al 2020 ; Liao et al 2022 ), morphological studies of herbarium specimens and plastid phylogenomic analyses, we concluded that these specimens are new to the genera Neottia ( Orchidaceae : Epidendroideae , Neottieae ), Papilionanthe and Gastrochilus ( Orchidaceae : Epidendroideae , Vandeae, Aeridinae ) respectively. These species are analyzed and described below.…”
Section: Introductionmentioning
confidence: 83%
“…We collected specimens of five previously unidentified species during our field surveys in Yunnan and Tibet from 2016–2023. Following a review of the literature (see Pearce and Cribb 2002 ; Chen et al 2009 ; Raskoti 2009 ; Jin and Pang 2016 ; Averyanov et al 2018 ; Wu et al 2019 ; Mu et al 2020 ; Liao et al 2022 ), morphological studies of herbarium specimens and plastid phylogenomic analyses, we concluded that these specimens are new to the genera Neottia ( Orchidaceae : Epidendroideae , Neottieae ), Papilionanthe and Gastrochilus ( Orchidaceae : Epidendroideae , Vandeae, Aeridinae ) respectively. These species are analyzed and described below.…”
Section: Introductionmentioning
confidence: 83%
“…Gastrochilus comprises about 65 species mainly distributed in China, India and Sri Lanka through eastern Asia and southern Japan to southeast Asia ( Liu et al., 2016 ; Wu et al., 2019 ) . Gastrochilus is characterized by having the lip divided into a semi-globose to saccate hypochile and broadly triangular or flabellate, often hairy or papillose epichile ( Tsi et al., 1996 ; Pridgeon et al., 2014 ; Liu and Gao, 2018 ).…”
Section: Taxonomic Treatmentmentioning
confidence: 99%